A Gene Panel for Early Identification of Future Responders to Immune Checkpoint Blockade - Panda, Anshuman; Betigeri, Anil; Ganesan, Shridar (Frontiers in Genetics, 2022)
Immune checkpoint blockade (ICB), therapies that target the PD-1 pathway, CTLA-4 pathway, and other checkpoint pathways, lead to durable responses in many cancer types. Since only a minority of patients respond to ICB, it may be useful to identify the future responders early in the course of treatment. In this study we evaluated a small (15 genes) biologically motivated panel, consisting of genes involved in immune activation and checkpoint pathways, for early identification of future responders to ICB. The panel passed consistency check, pathological and in-silico validations, and was an excellent predictor (area under ROC curve > 0.95) of eventual response to ICB, both CTLA-4 and PD-1 blockade, when applied to metastatic melanoma patients undergoing ICB (i.e. “on-treatment”) in a publicly available dataset. These results suggest that this small biologically motivated panel may be useful for early identification of future responders to ICB.